Synthesis and Characterization of Chemically and Green-Synthesized Silver Oxide Particles for Evaluation of Antiviral and Anticancer Activity - Muhammad Asif; Wajeeha Iqbal; Muhammad Fakhar-; Zahid Hussain; Malik Saadullah; Mudassir Hassan; Javed Rehman; Kholood A. Dahlous; Noora H. Al-Qahtani (MDPI AG, 2024)
Silver oxide (Ag2O) particles are wonderful candidates due to their unique properties, and their use in a wide range of research, industrial and biomedical applications is rapidly increasing. This makes it fundamental to develop simple, environmentally friendly methods with possible scaling. Herein, sodium borohydride and Datura innoxia leaf extract were applied as chemical and biological stabilizing and reducing agents to develop Ag2O particles. The primary aim was to evaluate the anticancer and antiviral activity of Ag2O particles prepared via two methods. XRD, UV-visible and SEM analyses were used to examine the crystallite structure, optical properties and morphology, respectively. The resulting green-synthesized Ag2O particles exhibited small size, spherically agglomerated shape, and high anticancer and antiviral activities compared to chemically synthesized Ag2O particles. The MTT (3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium-bromide) assay of green-synthesized Ag2O particles showed high anticancer activity against MCF-7 cells with IC50 = 17.908 µg/mL compared to chemically synthesized Ag2O particles with IC50 = 23.856 µg/mL. The antiviral activity of green-synthesized Ag2O particles and chemically synthesized Ag2O particles was also evaluated by a plaque-forming assay, and green-synthesized Ag2O particles showed higher antiviral ability with IC50 = 0.618 µg/mL as compared to chemically synthesized Ag2O particles with IC50 = 6.129 µg/mL. We propose the use of green-synthesized Ag2O particles in cancer treatment and drug delivery.